(دور دراسة علم المعاني لدى طلاب مستوى ثاني الكلية في فهم الأساليب البلاغية في سورة البقرة (النهي نموذجا - YANTO (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2016)
In order to obtain the data neened to finish this recesh the recesh used the descriptive analysis method based on this method the researcher attempted to gather the verses which contained asâlib an-nahyi in the surat Al-Baqarah, the described and analysed after that the researcher analysed, the influences in studying ‘ilmu ma’âni for the university students of the scond semester in the study program of Arabic education STIBA Ar Raayah in understanding uslûb an-nahyi al-balâghi, lastly the researcher applied the data obtained from the analysis of uslûb an-nahyi al-balaghi in the surat Al Baqarah and give his opinios about the teching metods used to learn balaghah knowledge to understanding the al-asâlîb al-balâghiyyah in the Al Qura’n Al Karîm. Balaghah knowledge is a branch from the branches of Arabic knowledge and is a one of the knowledges that is very urgent; because it is a knowledge for understanding the Al Qur’an Al Karîm and the secrets in its verses. This research is aimed to understand how far the influences are of studying ‘ilmu ma’âni for the university students of the scond semester in the study program of Arabic education STIBA Ar Raayah understanding uslûb an-nahyi al-balâghi in the surat Al Baqarah and to give their opinions on how to learn ‘ilmu balâghah in understanding al asâlîb al balâghiyyah in the Al-Quar’an Al Karîm. The results of this research shows that there are several uslûb al-balâghi in the surat Al Baqarah, and that studying ‘ilmu ma’âni in the surat Al Baqarah has a big influence in understanding uslûb an-nahyi in the Al Qur’an Al Karîm , also this research shows that in the analysis of uslûb an-nahyi al-balâghi can be benefit from in teaching balaghah knowledge.